Design And Construction Of Anaerobic Digester For Biogas Production. - CHIGOZIE, ACHEBE; UCHENNA, UCHECHUKWU CLINTON (My University, 2023)
Biogas production from waste could be one better way  addressing the issues of waste management and energy problem  in Nigeria. Biogas produced through the proper waste  management in an anaerobic digestion has a huge potential to  be an alternative source of energy to fossil fuel. In this project,  a 200 liter capacity batch sheet metal biogas plant operated at  mesospheric temperature under 40 day hydraulic retention time,  Fabricated at Mechanical engineering Fabrication center, Federal  Polytechnic Nekede, Owerri, Imo State was used for biogas  production of from agricultural waste (pig dung, cow dung,  poultry dropping) and kitchen waste. 21.25kg of each waste was  mixed with water of same weight at a ratio of 1:1 and charged.  The pressure of the slurry was monitored for a certain period of  time. The sample gags production was passed through the gas  chromatography to determine the percentage composition (mol% dry basis) of the biogas content. The result of biogas before  refining were 58.10 mol% dry CH4, 35.9mol% dry CO2 and 0.99  mol% dry H2S, which conformed with literature values of 50-70%  mol dry CH4, 30-40% mol dry CO2 and 0-3% mol dry H2S 58.15%  mol dry N2, 0.02% mol dry O2, 0.05% mol dry NH3, 0.47% mol  dry H2.
Keywords: Biogas Digester; Digester Stand; Discharge Valve